Trade, testing and toasters: Conformity assessment procedures and the TBT Committee - Devin McDaniels; Marianna Karttunen (World Trade Organization (WTO), 2016)
Even if traders adapt to technical regulations and standards in an export market, they still must prove compliance by undergoing conformity assessment procedures (CAPs), such as testing, inspection, or certification. Duplication, delays or discrimination in CAPs can significantly increase trade costs, and this risk is reflected in the growing importance of CAPs in WTO discussions and bilateral and regional free trade agreements. This paper conducts an empirical study of the trade issues that WTO Members encounter with CAPs as described in specific trade concerns (STCs) raised in the WTO Committee on Technical Barriers to Trade (TBT) during 2010-2014. We observe that CAPs raise proportionally more concern among WTO Members than technical regulations do, and that testing and certification are the procedures that most frequently give rise to trade problems. Within the framework of the TBT Agreement, we find that questions around transparency and whether CAPs create unnecessary barriers to trade are the two most prominent issues highlighted by Members.
Keywords: F13; F53; F55; K33; L15; L51; 330; international trade; certification; testing; conformity assessment procedures; international standards; international cooperation; coherence; non-tariff barriers; technical barriers to trade; regulation